2010
DOI: 10.1094/pdis-94-9-1137
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Carbendazim-Resistant Isolates of Gibberella zeae

Abstract: Sensitivity of Gibberella zeae to carbendazim was determined by measuring mycelial growth in fungicide-amended media. Among 1,529 isolates tested, 31 isolates showed a high level of resistance (HR) to carbendazim (fungicide concentration that results in 50% inhibition of mycelial growth [EC50] of 10.35 to 30.26 mg a.i. liter–1) and 10 isolates were moderately resistant (MR) (EC50 of 4.50 to 7.28 mg a.i. liter–1). The remaining 1,488 isolates were sensitive to carbendazim and were unable to grow on potato dextr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 14 publications
5
60
1
Order By: Relevance
“…Several studies have been conducted to explore the functions of b-tubulins in this pathogen. The resistance to MBC fungicides is caused by point mutations in the b2-tubulin [19,20]. Deletion of the b2-tubulin resulted in reduced conidiation, vegetative growth and pathogenicity, but increased sensitivity to carbendazim [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to explore the functions of b-tubulins in this pathogen. The resistance to MBC fungicides is caused by point mutations in the b2-tubulin [19,20]. Deletion of the b2-tubulin resulted in reduced conidiation, vegetative growth and pathogenicity, but increased sensitivity to carbendazim [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…So far, five resistant genotypes of FGSC have been characterized. Based on the previous reports (more than 10,000 isolates tested) in China (Duan et al, 2014; Liu et al, 2010; Liu et al, 2014), F167Y was predominant (>80%), followed by E198Q and F200Y. These three genotypes covered 99.99% tested resistant isolates.…”
Section: Discussionmentioning
confidence: 78%
“…Several studies report that F167Y was the most common resistant genotype (Chen et al, 2009; Liu et al, 2010). In this study, we also found F167Y to be the predominant resistant genotype in both Jiangsu and Anhui Province followed by E198Q and F200Y.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations